2019
DOI: 10.1186/s43042-019-0016-3
|View full text |Cite
|
Sign up to set email alerts
|

The association between angiotensin II type 1 receptor A1166C gene polymorphism and the risk of essential hypertension: a meta-analysis

Abstract: Background: Since first reported having the association with essential hypertension, angiotensin II type 1 receptor (AT1R) A1166C was globally investigated worldwide. However, controversy was found. Furthermore, previous metaanalyses did not adequate to clarify the precise correlation due to some limitations. Therefore, we aimed to perform a meta-analysis concerning the association between AT1R A1166C single-nucleotide polymorphism (SNP) and the risk of essential hypertension with eliminating the limitations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
2
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 75 publications
0
2
0
1
Order By: Relevance
“…Similarly, among north Indian patients with ID + DD ACE and 1166AC + CC AGTR1 , the combined genotype had a much higher risk of acute myocardial infarction than with II ACE and the 1166AA AGTR1 combined genotype [ 35 ]. Furthermore, the meta-analysis showed that the C allele and AC genotype of AGTR1 was associated with an increased risk of essential hypertension, while a decreased risk of essential hypertension was observed in the A allele and AA genotype [ 36 ]. However, it is worth noting that, in the Swedish population, it was reported that the interaction between the AC/CC AGTR1 and DD ACE genotypes is a predictor of survival for patients with HF [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, among north Indian patients with ID + DD ACE and 1166AC + CC AGTR1 , the combined genotype had a much higher risk of acute myocardial infarction than with II ACE and the 1166AA AGTR1 combined genotype [ 35 ]. Furthermore, the meta-analysis showed that the C allele and AC genotype of AGTR1 was associated with an increased risk of essential hypertension, while a decreased risk of essential hypertension was observed in the A allele and AA genotype [ 36 ]. However, it is worth noting that, in the Swedish population, it was reported that the interaction between the AC/CC AGTR1 and DD ACE genotypes is a predictor of survival for patients with HF [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, our findings support an association between the AGTR1 A1166C gene polymorphism and HCM risk under the dominant model, as well as an association with DCM under the allelic and dominant models. Previous meta-analyses confirmed the association of the AGTR1 A1166C polymorphism with coronary heart disease [62,63] and essential hypertension [64]. However, only limited studies have investigated its relationship with cardiomyopathy.…”
Section: Plos Onementioning
confidence: 92%
“…Moreover, to determine the association and effect estimates, data on allele and genotype frequency from selected papers were used to calculate the odds ratio (OR) and 95% confidence interval (95%CI). The protocols in our current study include paper selection, data extraction, quality assessment, and statistical analysis referred to our previous studies [14][15][16][17][18] , and we also used the checklist of the Preferred Reporting Items for Systematic Review and Meta-Analysis (PRISMA) to guide the protocols in our study 19 . A completed PRISMA checklist for the current study is available (DOI: https://doi.org/10.6084/m9.figshare.12016782) 98 .…”
Section: Methodsmentioning
confidence: 99%